Influence of vitamin D supplementation on immune function of healthy aging people: A pilot randomized controlled trial - Dong, Honglin; Asmolovaite, Viktorija; Farnaud, Sebastien; Renshaw, Derek (Frontiers in Nutrition, 2022)
Objectives: This study aims to investigate the influence of vitamin D supplementation on immune function of healthy older adults. Methods: Designed as a randomized control trial, 21 participants (55-85 years) completed the study during May-November 2018 in Coventry, England. The participants were randomized into vitamin D or the control group, stratified by age, gender and body mass index. The vitamin D group (n=12) took vitamin D3 tablets of 1000 IU/day for 12 weeks plus vitamin D education leaflet, while the control group (n=9) were only provided with the leaflet. At baseline, 6 weeks and 12 weeks, plasma 25(OH)D levels and immunological and metabolic parameters including phagocytic activity of granulocytes and monocytes, tumor necrosis factor, interleukin 6, lymphocyte subsets and fasting blood glucose and lipid were measured. Dietary vitamin D intake was analyzed at baseline and week 12. Data were presented as mean ± SD. Two-way repeated measures ANOVA and independent t-test were used to analyze the data. Results: At baseline, 42.9% of the participants were vitamin D deficiency (25(OH)D<25 nmol/L), only 10% achieved a level of 25(OH)D>50 nmol/L. Overweight/obese participants (n=9) had significantly lower mean plasma 25(OH)D concentration (22.3 ± 8.7 nmol/L) than normal weight participants (48.1 ± 34.3 nmol/L) (P=0.043). There was a significant increase in plasma 25(OH)D concentration in vitamin D group compared with that in control group (P=0.002) during the intervention period. The plasma 25(OH)D concentration in vitamin D group was increased at 6 weeks (from 38.4 ± 37.0 nmol/L at baseline to 51.0 ± 38.2 nmol/L) with little change observed between 6 and 12 weeks (51.8 ± 36.4 nmol/L). The plasma creatinine concentration in vitamin D group was significantly decreased compared with the control group (P=0.036) (79.8 ± 7.0 μmol/L at baseline vs 75.1 ± 5.4 μmol/L at week 12). No significant effect of vitamin D supplementation was determined on immunological parameters. Conclusions: Vitamin D deficiency is common among the aging population in the UK even during the summertime. Vitamin D supplementation at 1000 IU/day for 12 weeks significantly increased plasma 25(OH)D concentration but showed no effect on metabolic and immunological parameters except decreased plasma creatinine.